Assessment of the Population Status Libelloides Macaronius Scopoli, 1763 (Neuroptera, Ascalaphidae) In Tajikistan (London Journal of Research In Science: Natural and Formal, 2024)
New data on the state of the Libelloides macaronius Scopoli, 1763 population, based on our three-year monitoring in Tajikistan, are presented. It has been shown that the state of the population of this species is stable and there is no need for further measures taken to preserve its population. The presented data is necessary for the prepared new edition of the Red Book of the Republic of Tajikistan, since Libelloides macaronius is listed in the previous edition of the Red Book of Tajikistan. In addition, data on other species of owlflies collected by us during the expedition to the Pamirs in 2024 are provided.
Keywords: Drug; Blood; Immunoassay; chemiluminescence; biochip; Art; Good Living; Communities; Design; Education.; Population; Morphology.; Ascalaphidae; status; monitoring; Tajikistan.